Padre padrone - Macchi, Egisto 1928-1992 (Arrow Films, 2007)
The movie is the tale of a young, barely literate shepherd boy, who lives under the thumb of his tyrannical and brutal peasant father. Rescued from his family and his isolated lifestyle when called for military service, the boy eventually emerges as a brilliant scholar.
Orig.: I 1977. - Sprache: Ital. - Untertit.: Engl. - Enth.: Talking about cinema: The Taviani brothers / by Carlo Lizzani, 84 Min.
Keywords: Feature films -- Italy; Italien